ChemInform Abstract: K2Hg2Se3: Large‐Scale Synthesis of a Photoconductor Material Prototype with a Columnar Polyanionic Substructure. Issue 31 (August 2015) - Thiele, Guenther; Lippert, Sina; Fahrnbauer, Felix; Bron, Philipp; Oeckler, Oliver; Rahimi‐Iman, Arash; Koch, Martin; Roling, Bernhard; Dehnen, Stefanie
Abstract K2Hg2Se3 is prepared in a 50 g per batch scale by thermal fusion of K2Se and HgSe in 1:2 ratio (O2/methane burner, silica glass ampoule, 10 min) and subsequent solvothermal treatment in ethylenediamine (autoclave, 150 °C, 2 d; 94% yield).